ANALYSIS OF MOBILE TELECOMMUNICATION PATH LOSS IN RURAL COMMUNITIES - ALEXANDER OKANDEJI; FRANK ONAIFO; MATHEW OLAJIDE; AYODEJI OKUBANJO; HEZEKIAH FASANYA (Journal of Engineering Studies and Research)
In this work, a cheaper alternative method of determining path loss using Network cell info lite software is proposed. Hata-Okumura model is used in the determination of path loss and signal strength of mobile communication devices within Ibogun and Ifo, a suburban community in Ogun state, Nigeria. Additionally, this paper is also aimed at determining the path loss under transmission line to ensure proper network planning in areas covered by transmission lines. Result obtained shows that areas with pylons have greater path loss compared to areas with no pylons. It is recommended that the power levels of base station operating in this area should be increased.